“Atlantification” as a Possible Cause for Reducing of the Sea-Ice Cover in the Nansen Basin in winter - P. V. Aksenov; V. V. Ivanov; П. В. Аксенов; В. В. Иванов (Arctic and Antarctic Research, 2018)
The paper presents arguments in favor of an explanation of the reduction of the ice-covered area in the Nansen basin of the Arctic Ocean (AO) in winter by the so-called “atlantification “ — the strengthening of the influence of waters of Atlantic origin on the hydrological regime of the Arctic Ocean. We hypothesize that the main agent of “atlantification” in theWesternNansenBasinis winter thermal convection, which delivers heat from the deep to the upper mixed layer, thus melting sea ice and warming the near-surface air. To check up this hypothesis we used ocean reanalysis MERCATOR data for time interval 2007–2017. The quantitative criterion of thermal convection, based on the type of vertical thermohaline structure in the upper ocean layer, was applied to access the change of convection depth between climatic values in 1950–1990 and the present time. The main conclusion of the paper can be summarized as the following. Due to a gradual reduction of sea ice in the 1990s, the vertical stratification of waters in theWesternNansenBasinhas changed. As a result, the potential for penetration of vertical thermal convection into the warm and saline Atlantic layer and the consumption of heat and salt content of this layer for warming and salinification of the overlying waters increased, thus leading to additional loss of sea ice in winter. В статье представлены аргументы в пользу объяснения сокращения площади ледяного покрова в бассейне Нансена Северного Ледовитого океана (СЛО) в зимний сезон так называемой «атлантификацией». Хотя сам термин был изначально введен в обращение применительно к гидрофизическим процессам в Баренцевом море, в последние годы он все чаще употребляется для обозначения усиления влияния вод атлантического происхождения на гидрологический режим СЛО. Согласно представленным в статье результатам, основным агентом «атлантификации» в бассейне Нансена выступает зимняя термическая конвекция, обеспечивающая эффективный вертикальный теплообмен между теплым слоем атлантической воды и верхним ...